Role and CT and MR signs of focal congestion in development and course of stroke - S. Ye. Semyonov; M. G. Shatokhina; A. N. Nekhorosheva; A. A. Khromov; Ye. A. Zhuchkova; I. V. Moldavskaya; Yu. M. Portnov; A. V. Kovalenko; L. S. Barbarash (Бюллетень сибирской медицины, 2012)
CT and MR patterns of focal perfusion and diffusion disorder are compared in groups of patients with nonhemorrhagic venous and ischemic stroke, as well as in control group with chronic brain ischemia. The rMTT(+ vs. ++), rCBF (± vs. – –), rCBV (+ vs. ±), rDWI (± vs. +), and rADC (+ vs. –) patterns are determined as reliably distinguishable (p < 0.05), which is indicative of congestion in venous stroke focus as a releaser of pathophysiological mechanism of development of secondary ischemia.